PERBANDINGAN BUSANA TOKOH SRI KRESNA PADA RELIEF KRESNAYANA CANDI WISNU PRAMBANAN DAN CANDI INDUK PANATARAN - Waridah Muthi’ah; Agus Sachari; Kahfiati Kahdar (Fakultas Komunikasi, Sastra, dan Bahasa, 2014)
Kresna, hero and deity of Mahabharata legend, played major role as one example of morality and wisdom in Javanese traditional art and literature. Related with his status and identity as avatar of Vishnu, his traditional portrayal in India based on canon such as Manasara and Silpasastra. In Classical Java, he has been portrayed in Kresnayana reliefs on Vishnu Temple, Prambanan Complex and Main Temple, Panataran Complex. In those reliefs, his images were not strictly followed the canon, especially in costumes. Kresna’s appearance on Prambanan Temple showed different details in costumes, headgear, and accessories in comparison with Panataran Temple. Reliefs in Prambanan looked more similar with Krishna’s images influenced by 7th and 8th century Pallava art, in both carving style and costumes wore by the character, while reliefs in Panataran showed some indigenous characteristics. This research focused to compare Kresna’s portrayal diachronically in those temple, by using descriptive, comparative, and historical methods. It concluded that transformation of Kresna’s image went parallel with transmigration of power center to East Java, which followed by the development of macrocosmos-microcosmos parallels, as indicated by the depiction of king as deity and the culmination of Vishnu’s worships. The variations of Kresna’s image not only brought diversity based on local influence, but also engendered new system, which later developed into the basis of traditional Javanese art and king’s apparels